EFEKTIFITAS KINERJA PEGAWAI NEGERI SIPIL (PNS) DI KANTOR KECAMATAN SIMPANG RIMBA KABUPATEN BANGKA SELATAN (DITINJAU DARI UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - Virna Dewi (Justici, 2020)
Abstract Effectiveness is a measure of an organization, where the organization's ability to achieve all its needs. This means that the organization is able to organize and organize employee resources to achieve goals. Human Resources (HR) is a central factor in an organization. Whatever the shape and purpose, the organization is made based on various visions for human interests and in the implementation of its mission is managed and managed by humans. From the results of research conducted by researchers that the application of Law No. 5 of 2014 in Simpang Rimba sub-district, South Bangka Regency, overall service in the office has been good or has been effective but still needs to be maximized again